SENSITIVITY AND SPECIFICITY OF 24 HOURS URINARY 3-METHOXYTYRAMINES IN THE DIAGNOSIS OF MALIGNANT PHEOCHROMOCYTOMA AND PARAGANGLIOMA. (June 2018) - Barigou, M.; Billaud, E.; Requeplo, A.P. Gimenez; Baron, S.; Bobrie, G.; Zinzindohoue, F.; Blanchard, A.; Azizi, M.; Amar, L.
Abstract: Objective: At least 10% of pheochromocytoma and sympathetic paraganglioma (PPGL) are malignant, yet there is no specific biomarker of malignancy. Societies guidelines sugget the use of 3 Methoxytyramines (3MTT) for the diagnosis of malignancy, however few studies evaluated 24H-urinary 3MTT as a predictor of malignancy. The aim of this study was to evaluate the sensitivity/specificity of 24H-Urinary 3MTT for the diagnosis of malignant PPGL Figure. No caption available. Design and method: We conducted a retrospective study of electronic registers of Hypertension excellence center of Georges Pompidou hospital, from 2012 to 2015 to identify patients who completed PPGL-workup: Measurement of 24H-Urinary metanephrines/Normetanephrines(MTN/NMT) and 24H-Ur 3MTT by LCMS, Imaging exams to confirm/exclude PPGL, histopathological diagnosis of PPGL after surgery. We excluded from our analysis patients without the diagnosis of PPGL, under medications interacting with MTN/NMT/3MTT secretion, or without 24H-Ur 3MTT determination Determination of 24H-Ur MTN/NMT/3MTT was made by LCMS method with validated protocol. We first analysed ROC parameters for 24h-Ur 3MTT, then those of 24H-Ur 3MTT to 24H-Ur creatinine ratio. Results: 47 patients were included in this study:8 malignant PPGL and 39 non malignant PPGL. ROC curve of sensitivity(1-specificity) of 24h-Ur 3MTT for the diagnosis of PPGL malignancy showed an area under curve(AUC) of 0.671[95%CI 0.519–0.801]: The optimal criterion of the curve corresponded to a value of 24h-Ur 3MTT of 4.67 μmol/24 h and showed a specificity of 82.05% and sensitivity of 62.5% for malignancy diagnosis. A value > 12 μmol/24 h of 24h-Ur 3MTT offered 100% specificity with 37.5% of sensitivity ROC curve of sensitivity(1-specificity) of 24h-Ur 3MTT/24h-Ur Creatininuria for the diagnosis of PPGL malignancy showed an AUC of 0.774 [95%CI 0.629–0.883]: The optimal criterion of the curve was 1.25 μmol/mmol with a specificity of 94.87% and a sensitivity of 50% for the diagnosis of malignancy. A value of 24h-Ur 3MTT/Cr > 1.73 μmol/mmol offered 100% specificity with 25% sensitivity. Conclusions: These data sugget that 24h-Urinary 3MTT measured by LCMS and 24h-Ur 3MTT to creatinine ratio could be used as valuable biomarkers for the diagnosis of malignant PPGL. Values superior to 4.67 μmol/l and 1.25 μmol/mmol respectively offered the best compromise between high specificities and average sensitivities.